(untitled) (Revista Archai, 2018)
As all the pre-Socratic, Parmenides became interested in the study of the phusis, and consider he as a philosopher phusikos is natural. L. Rossetti, in his cappolavoro in two volumes Un altro Parmenide (Diogene Multimedia, Bologne, 2017), studied exhaustively the question. However, the perspective from which Rossetti faces the problem, not solve two major obstacles: the place of the “physical” texts in the so- called “doxa of mortals”, and the negative character that it has to Parmenides. Dependent on the arbitrary division of the poem in two sections, proposed in 1795 by G.G. Fülleborn, “physical” texts of Parmenides would thus correspond to a “deceiver speech of words” , which begins in verse 8.51 and ends in the Br. 19, speech that would diminish the positive character that physics has for Parmenides. The only way to claim the existence of a “Parmenides phusikos” consists of take off the fragments “physical” of those in which the goddess exposes “the opinions of mortals”, which criticizes. Obviously, this hypothesis implies a critical review of the doxographical tradition, that begins with Aristotle.